Solvent Extraction of Titanium(IV) with Organophosphorus Extractant from Chloride Solutions - Ma, Chunlei; Guo, Xianghai; Bai, Peng (Asian Journal of Chemistry, 2014)
The organophosphorus extractants for extraction of Ti(IV) from chloride solutions were introduced, mainly including acidic organophosphorus extractants such as D2EHPA, EHEHPA, Cyanex 272, Cyanex 302, Cyanex 301 and neutral organophosphorus extractants like Cyanex 923 (TRPO), tri-octyl phosphine oxide (TOPO) and tri-n-butyl phosphate (TBP). The extraction behaviours like extraction mechanism, extraction equilibrium, loading capacity, stripping behaviour and selectivity were reviewed, along with the effect of acidity, diluent and metal concentration to Ti(IV) extraction. The Ti(IV) extraction equilibrium time with acidic organophosphorus extractants is more than 1 h except Cyanex 302 and Cyanex 301 with which less than 5 min are required to reach equilibrium. The Ti(IV) extraction kinetics with neutral organophosphorus extractant is also fast: the extraction reaches equilibrium within 3-5 min. Stripping Ti(IV) from loaded acidic organophosphorus extractants is difficult, while from neutral ones is much easier. Compared to neutral organophosphorus extractants, the practical application of acidic organophosphorus compound is difficult for Ti(IV) extraction due to their slow extraction equilibrium and difficulty in stripping and neutral organophosphorus extractants could be used to separate both Fe(III) and Ti(IV) from other metal impurities. TBP could be used for separation Fe(III) from Ti(IV) and other metal ions.